Microbiological hazards in fresh leafy vegetables and herbs meeting report. (Microbiological risk assessment series ;, 2008)
Problems linked with pathogens in fresh produce, including the associated public health and trade implications, have been reported in a number of countries worldwide. Furthermore, from 1980 to 2004, the global production per annum of fruit and vegetables grew by 94% and they are a critical component of a healthy diet. Reported outbreaks associated with leafy vegetables and herbs have been notable for the wide geographical distribution of the contaminated products, the high numbers of consumers exposed and thus the large number of cases. This meeting addressed the pathways for contamination, survival and persistence of microbiological hazards associated with leafy vegetables and herbs, and the potential management options from primary production through to the consumer.--Publisher's description.